From Biomass Waste to Functional Iron Oxides: Mechanistic Understanding, Structure Engineering, and Environmental Applications - Dewi Kurnianingsih Arum Kusumahastuti; November R. Aminu; Agung R. Gintu; Emmanuel Hernanda Yustisia Susanto; Gecia Ovi Wulandari (Postgraduate, University of Mataram, 2026)
Biomass-mediated green synthesis of iron oxide nanomaterials has gained increasing attention as a sustainable alternative to conventional chemical methods, offering lower energy requirements, reduced chemical toxicity, and intrinsic surface functionalization. Unlike previous reviews that mainly summarize synthesis routes or environmental applications separately, this review establishes an integrated structure–property–performance framework to systematically correlate biomass chemistry, phase evolution, and functional remediation behavior of iron oxide nanomaterials. A structured scoping review was conducted by analyzing 42 peer-reviewed articles published between 2010 and 2024, selected from major scientific databases using predefined inclusion criteria emphasizing crystalline phase identification, quantitative structural characterization, and measurable environmental performance. Comparative synthesis of the collected data reveals that phytochemical constituents, particularly polyphenols and organic acids, regulate Fe³⁺ reduction, chelation equilibria, nucleation kinetics, and phase selectivity among Fe₃O₄, γ-Fe₂O₃, and α-Fe₂O₃. Fe₃O₄-rich systems exhibited smaller particle sizes (10–30 nm), higher saturation magnetization (30–70 emu g⁻¹), and superior pollutant removal efficiencies (90–99%), while γ-Fe₂O₃ showed moderate magnetic properties (20–50 emu g⁻¹) and α-Fe₂O₃ displayed larger particle sizes (30–60 nm), lower magnetization (<2 emu g⁻¹), but greater thermodynamic stability. Adsorption capacities ranged from 30–250 mg g⁻¹ depending on pollutant type and phase composition. Despite these promising performances, variability in biomass composition, phase instability, and inconsistent testing protocols remain major barriers to reproducibility and scalability. This review provides a quantitative and mechanistic framework to guide rational synthesis design, improve reproducibility, and accelerate scalable deployment of biomass-derived iron oxide nanomaterials for environmental remediation.